Specific physical test for higher elite speed climbers - Andrey , Shunko (Journal of Sports Research, 2025)
This study aims to identify significant physical tests for elite male speed climbers. By analyzing existing research and testing methods, we develop a reliable test battery to assess and monitor physical preparedness in competitive speed climbing. The study included 10 elite Russian national team climbers and a comparative group of 24 lower-level athletes. The test battery covered power, speed, coordination, and flexibility. Tests included the countermovement jump (JHT), Laffaye upper limb test, tapping test, and forward bend test. Statistical analysis using Pearson’s correlation assessed the significance of each test in relation to climbing performance. Four key tests demonstrated strong correlations with speed climbing performance: JHT (r=0.933, p=0.012), Laffaye test (r=0.897, p=0.007), tapping test (r=0.821, p=0.009), and forward bend (r=0.967, p=0.001). These tests effectively differentiate elite climbers and provide a standardized method for assessing physical readiness. The identified tests can be used to monitor and enhance training programs for speed climbers. Express testing allows for rapid assessment, benefiting both elite and developing athletes. Coaches and athletes can use these tests to track performance, tailor training strategies, and identify talent. The results support structured physical preparation in speed climbing.